Communication within the Selected Labour Office - Fuka, Jan; Kopáčková, Zuzana; Brodský, Zdeněk (International Business Information Management Association-IBIMA, 2018)
This paper is focused on the analysis of communication possibilities of the Labour Office of the Czech Republic. Firstly, a theoretical research of the issue is provided in order to build the foundation for the practical part. Then it characterizes the communication within the process of employment mediation. Afterwards, there is a detailed analysis of communication between the regional Labour Office in selected region, job seekers, private companies and municipalities. At the end of the paper the summary of analysis is provided together with proposals that could help to improve the communication possibilities within the Labour Office of the Czech Republic.
Komunikace v rámci vybraného úřadu práce
Keywords: Labour Office; communication; unemployment; employers; Úřad práce; komunikace; nezaměstnanost; zaměstnavatelé